Family formation and subjective well-being. A literature overview - Baranowska, Anna (Studia Demograficzne, 2010)
While most frequently cited economic models of family formation link partnership or parenthood decisions with the concept of maximisation of life-cycle utility, empirical research has so far assumed that life satisfaction represents a factor which cannot be measured directly. Empirical studies have therefore treated the utility derived from partnership and parenthood as universal and assumed that only the direct or opportunity costs of family formation produce variation in the observed fertility behaviour. The emerging literature treats the subjective wellbeing as a measure of utility and hence allows direct tests of hypotheses related to the impact of events in family career on life satisfaction. This article provides an overview of the leading theoretical concepts and the recent empirical evidence on the impact of family formation on subjective wellbeing. It surveys the studies which investigate effects of entry into union and entry into parenthood on subjective well-being. The focus is on studies that attempt to estimate the causal effects. Furthermore, the article discusses studies that consider various ways in which institutional and cultural factors can modify the impact of family formation on subjective well-being. Finally, some suggestions are formulated how the research in this fi eld could contribute to the debate on population policy. Consequently, and some topics for further research are proposed.